Sustainable Development and Soils in the Portuguese Education System: Open Problems and Further Challenges - Patrícia João; Maria Helena Henriques; Ana V. Rodrigues (MDPI AG, 2022)
The curricular documents for Basic Education Sciences in Portuguese schools (ages 6 to 15) that currently affect teachers and students across the world integrate Sustainable Development concerns regarding soils. A sharp gap emerges between the official documents and the teachers' perceptions of how to approach such issues. Urgent measures are required to bridge both worlds: reformulations of the official documents that guide teachers' practices and educational resources focused on soils from a Sustainable Development perspective. A new organization of the curricular documents for this theme that aims to promote quality education among Portuguese Basic Education schools worldwide is proposed.